2022
DOI: 10.1017/jfm.2022.876
|View full text |Cite
|
Sign up to set email alerts
|

Whirling instability of an eccentric coated fibre

Abstract: We study a gravity-driven viscous flow coating a vertical cylindrical fibre. The destabilisation of a draining liquid column into a downward moving train of beads has been linked to the conjunction of the Rayleigh–Plateau and Kapitza instabilities in the limit of small Bond numbers $Bo$ . Here, we focus on quasi-inertialess flows (large Ohnesorge number $Oh$ ) and conduct a linear stability analysis on a unidirectional flow along a rigid eccentric fibre for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…However, in this case, the viscosity is independent of shear rate; thus asymmetry must arise from a different mechanism. Recent work by Eghbali et al (2022) showed that shear along the liquid-gas interface of a Newtonian liquid can sustain asymmetric flows for thick, viscous films flowing down a fibre using an energy balance analysis. However, the asymmetry of a Newtonian bead-on-fibre pattern remains an open topic for investigation, and the mechanism responsible for amplifying and sustaining it has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in this case, the viscosity is independent of shear rate; thus asymmetry must arise from a different mechanism. Recent work by Eghbali et al (2022) showed that shear along the liquid-gas interface of a Newtonian liquid can sustain asymmetric flows for thick, viscous films flowing down a fibre using an energy balance analysis. However, the asymmetry of a Newtonian bead-on-fibre pattern remains an open topic for investigation, and the mechanism responsible for amplifying and sustaining it has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Eghbali et al. (2022) performed experiments on highly viscous Newtonian flow down a fibre, and observed two asymmetric modes: pearl and whirl. They altered the initial eccentricity of the liquid about the fibre, showing that the morphology depends on the Bond number and eccentricity, and rationalized these observations using an energy analysis that showed that shear at the liquid–gas interface can sustain the whirling mode instability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P.Yu's eccentric inertia coupling instability mechanism that the lateral and torsional motions may be stable only due to the eccentric inertia effect caused by the angle of attack change so that the response of the lift on the lateral vibration to form a positive feedback exacerbated the lateral vibration, and gradually accumulating energy, and finally the formation of a substantial dance. Theoretically speaking, vertical self-excitation or torsional self-excitation of a single degree of freedom is possible, but in fact, the wire dance belongs to the motion of three degrees of freedom, and in the vast majority of cases, three kinds of vibration, vertical, horizontal and torsional, will occur at the same time [23]. This is due to the presence of eccentric inertia of the wire over ice, where one motion may induce another.…”
Section: Eccentric Inertial Coupling Instability Mechanismmentioning
confidence: 99%